The teaching of Science and Biology and the new digital methodologies: Analysis of the conceptions of teachers and students in the school scope (Research, Society and Development, 2023)
Teaching Science and Biology tends to lead students to the relevance of thinking, transforming learning associated with technological resources into clarification and assimilation. Thus, this work aimed to evaluate the contributions of remote teaching and digital methodologies in the learning process in Science and Biology from the perspective of students and teachers of Elementary and High School, highlighting the importance of the technological tools used. The target audience consisted of elementary school students in the final years (6th and 9th) and high school, as well as science and biology teachers from a public school in the north of the state of Espírito Santo. The results corroborated the analysis of the perception of teachers and students with the use of digital technologies in remote Science and Biology classes, throughout the period of the COVID 19 pandemic. Thus, it was possible to reflect on the diversity of interpretations, as well as these resources has contributed to the learning of these disciplines.